Characterization of patients with bacterial community-acquired pneumoniaadmitted a provincial hospital in Pinar del Rio - Emilio Yaser Pando Hernández; Carlos Alfredo Miló Valdés; Migela Marrero Pérez; Víctor Manuel Mena Hernández; Humbelina Díaz Alfonso (Universidad Médica Pinareña, 2018)
Introduction: community-acquired pneumonia is an inflammation of the lung parenchyma caused by the uncontrolled reproduction of an acquired infectious agent in the out-hospital environment. It is not a unique process, but a group of infections of diverse etiology affecting different people where the condition, the epidemiology, as well as the clinical chart; makes the difference of its prognosis. Objective: o characterize a group of patients hospitalized for bacterial pneumonia acquired in the community. Method: an observational, descriptive and cross-sectional study was carried out in the Internal Medicine service at Dr. León Cuervo Rubio Teaching Surgical Clinical Hospital, Pinar del Río, from December 2016 to December 2017. The target group consisted of 376 patients, choosing a sample of 300 patients. Results: the age group over 71 years old was the most affected (38,0 %), female sex (58,3 %). Fever outweighed as clinical sign (72,3 %), heart failure (29,3 %) as a risk factor and hypertension (82,3 %) as comorbidity. Decompensate heart failure (56,3 %) was the most frequent complication. Conclusions: patients over 60 years of age and women who suffer from heart failure present a higher risk for community-acquired pneumonia. High blood pressure, heart failure and chronic obstructive pulmonary disease are common comorbidities in these patients. In addition, noninfectious complications such as decompensate heart failure can occur.